Trends in Incidence, Mortality, and Survival of Penile Cancer in the United States: A Population-Based Study - Deng, Xinxi; Liu, Yang; Zhan, Xiangpeng; Chen, Tao; Jiang, Ming; Jiang, Xinhao; Chen, Luyao; Fu, Bin (Frontiers in Oncology, 2022)
Purpure: To investigate the trends in incidence and mortality, and explore any change in survival of penile cancer in the United States. Methods: We obtained data from the Surveillance, Epidemiology, and End Results (SEER) database (2000–2018) utilizing SEER. Stat software. The joinpoint regression was used to analyze the secular trend of incidence and incidence-based mortality (IBM) stratified by age, race and summary stage. 5-year relative survival rate was also calculated. Result: The age-adjust rates of penile cancer patients were 0.38(0.37-0.39) and 0.21(0.2-0.21) for overall incidence and IBM, respectively. The 5-year relative survival rates were 67.7%, 66.99% and 65.67% for the calendar periods of 2000-2004, 2005-2009, and 2010-2014, respectively. No significant changes in incidence by era were observed from 2000 to 2018(Annual percentage change (APC)= 0.5%, P=0.064). The IBM rate of penile cancer showed an initial significant increase from 2000 to 2002(APC= 78.6%, 95%CI: -1.7-224.6) and then with deceleration rates of 4.6% (95% CI:3.9-5.3) during 2002 to 2018. No significant improvement in 5-year relative survival was observed. The trends by age, race and summary stage in the incidence and IBM were significantly different. Conclusion: This study, using population-level data from the SEER database, showed an increasing trend in incidence-based mortality and no significant improvement in the 5-year relative survival rate. Meanwhile, the incidence of penile cancer exhibited a relatively stable trend during the study period. These results might due to the lack of significant progress in the treatment and management of penile cancer patients in the United States in recent decades. More efforts, like increasing awareness among the general population and doctors and centralized management, might be needed in the future to improve the survival of this rare disease.